Pengaruh Penanganan Keluhan (Complain Handling) terhadap Kepercayaan Pelangan pada Minimarket Indomaret di Kota Bitung (Studi Kasus Indomaret Winenet) - Ratna Taliupan (Journal on Education, 2022)
This study aims to determine how much influence complaint handling has on customer trust in Indomaret minimarkets in the city of Bitung (a case study on Indomaret winenet), and the population and sample in this study were all Indomaret customers who gave complaints as many as 63 customers. The method used in this research is a quantitative method or method. And the data used in this study are primary data obtained from respondents by filling out a questionnaire that is measured using an ordinal measurement scale. The analysis technique used in this study is the research instrument test, classical assumption test, Simple Linear Regression Analysis, research hypothesis test, coefficient of determination. The analysis tool uses SPSS ver 2.6, the variables used in this study are complaint handling, customer trust. Based on the results of this study, the conclusions obtained are that variable (X) handling complaints has a positive and significant effect on variable (Y) customer trust.